Meninjau pemasangan kawat gigi dalam perspektif hukum Islam: Antara keperluan kesehatan dan tujuan estetika - Firdaus, Rubayyi (Maliki Interdisciplinary Journal, 2024)
This article reviews braces by considering an Islamic legal perspective, exploring the complex relationship between health needs and aesthetic goals. In the process of preparing this article, the author of the article used the library study method, namely by searching and collecting suitable and relevant sources. In understanding Islamic law, aspects of health and body care are important. Installation of braces is basically used to treat diseases such as uneven tooth structure, but recently it has become a trend for aesthetics or to beautify oneself, so that the law of straightening teeth with orthodontic treatment in an Islamic perspective can be known based on its aim, namely to improve the function of the teeth or simply beautify the appearance, this raises legal questions related to changing the creation of Allah SWT. This article explores Islamic legal perspectives on braces, considering arguments arising from primary legal sources, such as the Qur'an and Hadith. Apart from that, this article also explores the views of leading Islamic jurisprudence scholars regarding this issue, discussing the extent to which the act of installing braces is in accordance with Islamic principles, as well as considering aspects such as the intention, purpose and possible consequences of the procedure. By detailing Islamic law's view of braces, this article aims to provide a better insight into how modern medical practices regarding braces can be aligned with Islamic legal values.